Marine Fish Antifreeze Proteins: The Key Towards Cryopreserving The Winter Soldier - Suris-Valls, Roma; Mehmedbasic, Maja; Voets, Ilja K (Superhero Science and Technology, 2018)
Along the path to building knowledge and developing new technologies, scientific research is a fountain of reliable information that allows us to probe how entities in the natural world are likely to behave. For instance, several marine fish that inhabit sub-zero temperature waters use ice-binding proteins to prevent damage to their cells and tissues. The antifreeze properties of these ice-binding proteins might hold the key for future cryopreservation applications. The non-profit organization Organ Preservation Alliance (OPA) declared that one-fifth of donated kidneys are wasted and approximately two-thirds of donated hearts and lungs never make it to a patient. Advances in cryopreservation methods would enable us to significantly reduce this donor organs wastage – possibly saving the lives of more than 110,000 people who are currently on the organ transplant waiting list in the Unites States. The establishment of a large organ library could potentially lower the patient rejection response to the transplanted organ since a more suitable donor match would be feasible. In this article, we will give an insight on the different types of ice-binding proteins, their antifreeze properties and their potential role in the cryopreservation of organs while using the fictional character known as the Winter Soldier in the Marvel Cinematic Universe as our main protagonist.